The outcomes of outcomes and effectiveness research: impacts and lessons from the first decade. - Stryer, D (2000)
OBJECTIVE: To assess the outcomes of the Agency for Healthcare Research and Quality's (AHRQ; formerly the Agency for Health Care Policy and Research, AHCPR) first decade of focus on outcomes and effectiveness research (OER) and to identify needs and opportunities for the study of OER in the coming years. DATA SOURCE: Study findings were collected in response to an inquiry by the Center for Outcomes and Effectiveness Research at AHRQ in July 1997 to all principal investigators (PIs) funded between 1989 and 1997. The request was for investigators to identify their "most salient findings" and supply material for up to three slides. STUDY DESIGN: A taxonomy of 11 non-mutually exclusive categories was used to group the investigators' salient findings by characteristics of methodology or purpose. Two health services researchers assigned findings to up to three categories for each discrete study. PRINCIPAL FINDINGS: Responses were received from 61 (64 percent) of the 91 PIs, reporting on 115 studies. Of the 246 category assignments made, descriptive epidemiology was the most common (24 percent), followed by comparative effectiveness (17 percent) and economic assessments (12 percent). Most studies were retrospective analyses of administrative data. Viewed within a conceptual framework for assessing the impact of research, OER has built a solid foundation for future quality improvement efforts by identifying problems, generating hypotheses, and developing new methodologies and has had limited impact on health care policies, practices and outcomes. CONCLUSIONS: OER has had moderate but significant success meeting initial expectations for the field. Challenges for the next generation of OER include advancing from hypothesis generation to definitive studies of effectiveness, and acceleration of the process by which findings effect policy, practice, and outcomes.